Karakteristik Pasien Prolaps Uteri di RSUP Dr. Sardjito Yogyakarta Tahun 2013 - Hamamah, Jefi; Pangastuti, Nuring (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: Uterine prolaps suffer by nearly half population of women. Many factors related to the causes of prolaps. The pattern varies in different country and ages.Objective: To evaluate the characteristic of uterine prolaps patient in Sardjito Hospital in the period January – December 2013.Method: This is an analytic descriptive study that reviewed medical record of Sardjito Hospital within January - December 2013. Data was reported, tabulated dan presented in the form of risk factors, chief complains, grade of uterine prolaps and treatment, finally analysed.Result and Discussion: There were 30 cases of uterine prolaps from Obstetrics and Gynecology Sardjito Hospital within January-December 2013. Most of the patient age were 45-64 year (48.4%), parity more than 2 (73.3%), menopause (73%), vaginal delivery more than 2 (73%). Symptoms that mostly revealed was lump on the delivery passage (73.3%). Patient were mostly suffered from grade 4 uterine prolaps (43%). There were two types of treatment i.e. conservative and operative. Conservative treatment used Kegel exercises and pessarium. Operative treatment used total vaginal hysterectomy, colpocleisis, anterior and posterior colporaphy.Conclusion: The risk factors for uterine prolaps were older age, menopause, multiparity, vaginal delivery. The treatment mostly used total vaginal hysterectomy.Keywords: uterine prolaps, risk factors, vaginal hysterectomy